PRECEDE and PROCEED Model on the Determinants of Teacher’s Role in the Provision of Reproductive Health Education for Students with Mild Mental Retardation at School of Disability in Sleman, Yogyakarta - Putri Rahmasari; Ismi Dwi Astuti Nurhaeni; Endang Sutisna Sulaeman (Journal of Health Promotion and Behavior, 2016)
Background: Access to reproductive health information is lacking among students with mental retardation (MR). Teachers at the School of Disability have potentially important role in improving access to reproductive health information among students with MR. This study aimed to investigate the determinants of teachers role in the provision of reproductive health education for students with mild MR at School of Disability, in Sleman, Yogyakarta.Subjects and Method: This was a qualitative study with phenomenology approach, conducted at School of Disability, Sleman, Yogyakarta. Key informants were selected by purposive sampling (i.e. criterion sampling), consisting 7 teachers of disability school, 5 personnels from the District Office of Education and Sport. PRECEED and PROCEDE model was used as a framework to identify the determinants under study. The data were collected by in-depth interview, observation, and document review. The data were analyzed by Miles and Hubberman method.Results: The seven teachers have shown their good roles in the provision of reproductive health education. Factors that determined teachers role included knowledge, experience, attitude, subjective norms, perceived behavior control, external support, and availibility of resources. Weak perceived behavior control (e.g. perceived teacher’s incompetence) and negative subjective norms (e.g. teaching about reproductive health was considered taboo by the community) of the teachers weakened the teachers role. Lack of educational media, substandard rooms, reproductive health materials that were unintegrated in the curriculum, weakened teachers intention to perform their roles.Conclusion: Teachers at the school of disability in Sleman, Yogyakarta, have shown their good role in the provision of reproductive health education for students with mild MR. Knowledge, experience, attitude, subjective norms, perceived behavior control, external support, and availibility of resources, are important determinants of teachers role in the provision of reproductive health education.Keywords: teachers role, school of disability, mental retardation, studentCorrespondence: Putri Rahmasari. School of Midwifery, ‘Aissyiah University, Yogyakarta. Email: putrialzam@gmail.com.Journal of Health Promotion and Behavior  (2016), 1(2): 109-119https://doi.org/10.26911/thejhpb.2016.01.02.06